2017
DOI: 10.1007/s00420-017-1219-x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to respirable crystalline silica and chronic non-malignant renal disease: systematic review and meta-analysis

Abstract: BackgroundWhile occupational exposure to respirable silica is known to lead to lung disease, most notably silicosis, its association with chronic kidney disease is unclear.ObjectivesThis review explores the association between occupational exposure to respirable silica and chronic non-malignant renal disease such as glomerulonephritis. The evidence has been collected and compiled. Possible sources of bias are thoroughly discussed.MethodsCohort studies with silica exposure and case–control studies of renal dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…Several studies point out that the silica-exposed industrial workers can be exposed to highly toxic fresh crystalline silica generated during the processing of pottery products, ceramics, bricks, and tiles, while the general population could be exposed to amorphous aged silica particles with low toxicity. 1,3,28 A very recent interdisciplinary research relates the variable toxicity of silica particles to their surface chemistry. New physico-Early Nephrotoxicity Induced by Occupational Silica Exposure chemical methods can finely characterize and quantify silanols at the surface of silica particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies point out that the silica-exposed industrial workers can be exposed to highly toxic fresh crystalline silica generated during the processing of pottery products, ceramics, bricks, and tiles, while the general population could be exposed to amorphous aged silica particles with low toxicity. 1,3,28 A very recent interdisciplinary research relates the variable toxicity of silica particles to their surface chemistry. New physico-Early Nephrotoxicity Induced by Occupational Silica Exposure chemical methods can finely characterize and quantify silanols at the surface of silica particles.…”
Section: Discussionmentioning
confidence: 99%
“…The most common industries a r t i c l e and occupations that have the potential for silica exposure include mining, quarrying, foundry work, glass manufacture, ceramic, pottery, and cement production. 1 Silica dust was suspected to affect the human kidney over 90 years ago. The detected pathologic renal changes are similar to those induced by nephrotoxic heavy metals in the form of dose-related nephropathy that causes degenerative changes in tubular epithelium and interstitial inflammation, fibrous nephrosis, glomerulonephritis, and systemic vasculitis.…”
Section: Introductionmentioning
confidence: 99%
“…Nonbeneficial effects of DE: Available information on the non-beneficial effects of DE showed that people who work with crystalline form of diatomaceous earth in large amounts such as miners, quarrymen, smelters, sandblasters, masons, and ceramic and glass manufacturers are likely to have lung problems [132,133]. Due to their very small density, Silica nanoparticles can be readily evaporated into air, and can be inhaled.…”
Section: Potentials Of Fossil Shell Flourmentioning
confidence: 99%
“…Another environmental risk to the kidneys is crystalline silica, which is known to be related to chronic renal failure. Although the toxic effect of crystalline silica on the kidneys is not yet understood, many studies have investigated chronic kidney disease in exposed populations [ 40 ].…”
Section: Toxicity Of Particulate Matter Constituents On the Kidneymentioning
confidence: 99%
“…Crystalline silica dust has been studied in the context of several occupational and environmental disorders, such as lung cancer, scleroderma, systemic lupus erythematosus, rheumatoid arthritis, or antineutrophil cytoplasmic antibody-associated vasculitis. Möhner et al [ 40 ] conducted a meta-analysis exploring the association between respirable crystalline silica and nonmalignant renal disease. A total of 23 cohort and 4 case-control studies were included in the analysis.…”
Section: Toxicity Of Particulate Matter Constituents On the Kidneymentioning
confidence: 99%